Нідерландський досвід впровадження відновного правосуддя у кримінальному провадженні: перспективи для українського правосуддя (ПРАВОВІ ГОРИЗОНТИ, 2025)
The article analyzes the Dutch experience in implementing restorative justice and the possibilities for its adaptation in Ukraine. The relevance of the topic is determined by Ukraine’s European integration commitments and the need for post-conflict social cohesion. Comparative legal analysis and statistical cost assessment were used as methodological tools. The Netherlands was selected as a model case due to the widespread application of mediation and consistent state support. The study demonstrates that legislative comprehensiveness and procedural clarity significantly increase access to reconciliation. Centralized funding guarantees free services and strict selection of mediators. Moreover, large-scale information campaigns build public trust and professional support. Comparative data show that mediation is more cost-effective than traditional judicial proceedings, while simultaneously reducing the caseload of courts and accelerating conflict resolution. A distinctive contribution of the study is the formulation of comprehensive recommendations for Ukraine. The identified problems are analyzed through the lens of Dutch practice, with subsequent adaptation to domestic legal realities. Proposals include the allocation of stable state funding through redistribution of the court budget, as well as the development of educational programs and public awareness campaigns to overcome punitive justice stereotypes. The study argues that the adoption of the Dutch model could strengthen the humanistic vector of Ukraine's criminal policy.